2019
DOI: 10.1523/jneurosci.0435-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term, Targeted Delivery of GDNF from Encapsulated Cells Is Neuroprotective and Reduces Seizures in the Pilocarpine Model of Epilepsy

Abstract: Neurotrophic factors are candidates for treating epilepsy, but their development has been hampered by difficulties in achieving stable and targeted delivery of efficacious concentrations within the desired brain region. We have developed an encapsulated cell technology that overcomes these obstacles by providing a targeted, continuous, de novo synthesized source of high levels of neurotrophic molecules from human clonal ARPE-19 cells encapsulated into hollow fiber membranes. Here we illustrate the potential of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 74 publications
1
35
0
Order By: Relevance
“…While encouraging, subsequent studies should provide a more detailed analysis of striatal neuronal subtypes including more precise indices of individual neuron morphology and function. While not shown here, we have recently published several papers in animal models [ 31 , 32 ], including excitotoxic lesions [ 33 ], that used GFAP immunohistochemistry to confirm the lack of inflammatory response following trophic factor delivery for longer periods of time than demonstrated in the current studies. Immunohistochemistry was also used to confirm GDNF receptor engagement.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…While encouraging, subsequent studies should provide a more detailed analysis of striatal neuronal subtypes including more precise indices of individual neuron morphology and function. While not shown here, we have recently published several papers in animal models [ 31 , 32 ], including excitotoxic lesions [ 33 ], that used GFAP immunohistochemistry to confirm the lack of inflammatory response following trophic factor delivery for longer periods of time than demonstrated in the current studies. Immunohistochemistry was also used to confirm GDNF receptor engagement.…”
Section: Discussionmentioning
confidence: 85%
“…GDNF signals through a multicomponent receptor, first binding the GDNF family receptor α 1 (GFR α 1) with the resulting complex recruiting the transmembrane receptor kinase Ret or the neural cell adhesion molecule (NCAM) to initiate downstream signaling pathways. We found that treatment with GDNF dramatically increased the receptor expression and also highly increased RET phosphorylation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Significant fractions of transplant-derived cells expressed several neurotrophic factors having anticonvulsant properties such as GDNF, IGF-1, and FGF-2, which might have resulted in higher concentrations of anti-seizure proteins in the milieu of the epileptic hippocampus. Indeed, the role of these graft-derived neurotrophic factors in seizure suppression is corroborated by findings that seizure activity declined when the epileptic hippocampus was genetically or pharmacologically manipulated to contain higher concentrations of GDNF [ 53 - 55 ], IGF-1 [ 56 ] or FGF-2 [ 57 ]. Thus, NSC grafting resulted in an improved anti-seizure defense in the epileptic hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…The development of a delivery strategy is limited due to the blood-brain barrier; however, principle studies in animal models may offer new approaches including gene delivery, cell-based delivery, and also biomaterial drug delivery [61]. In the past year, several in vivo studies have been reported for neurodegenerative diseases [71,[74][75][76]. Galli et al used alginate-poly-L-lysine-alginate (APA) microcapsules and cross-linked the spheres with both Ca 2+ and Ba 2+ .…”
Section: Clinical Applicationsmentioning
confidence: 99%